Selective crowdsourcing for open process innovation in the public sector - are expert citizens really willing to participate? - Seidel, C. E.; Thapa, B. E.; Niehaves, Björn; Plattfaut, Ralf (Proceedings of the 7th International Conference on Theory and Practice of Electronic Governance, 2013)
In light of current challenges that modern societies are facing (e.g. demographic change, financial budgetary constraints, and demand for individualized public services), public administrations need to find innovative ways to deliver public services more efficiently. One possible solution to the dilemma of shrinking resources and increasing demands is open innovation. Various papers have already established the idea of crowdsourcing as a means of open innovation in the public sector. In order to enrich theory and practice in the field of collaborative innovation processes, this research focuses on the willingness of citizens to participate in crowdsourcing for innovation. More specifically, we highlight the role of expert citizens in selective crowdsourcing for complex tasks in the public sector with the concrete example of process innovations. We examine different levels of willingness to participate in crowdsourcing by means of a quantitative analysis of a questionnaire survey with n=128 German citizens. Our analysis shows that citizens are indeed motivated to participate in selective crowdsourcing to generate solutions to complex problems in the public sector. Although mobilizing adequate experts for complex tasks may seem challenging, we find that expert citizens actually have a higher willingness to collaborate on complex as well as simple tasks than non-experts. Additionally, financial incentives remain a relevant instrument in the design of citizensourcing projects. Ultimately, the role of age as an influence to participate in crowdsourcing will be discussed.